2016
DOI: 10.1111/1758-2229.12359
|View full text |Cite
|
Sign up to set email alerts
|

A temperate river estuary is a sink for methanotrophs adapted to extremes of pH, temperature and salinity

Abstract: SummaryRiver Tyne (UK) estuarine sediments harbour a genetically and functionally diverse community of methane‐oxidizing bacteria (methanotrophs), the composition and activity of which were directly influenced by imposed environmental conditions (pH, salinity, temperature) that extended far beyond those found in situ. In aerobic sediment slurries methane oxidation rates were monitored together with the diversity of a functional gene marker for methanotrophs (pmoA). Under near in situ conditions (4–30°C, pH 6–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 55 publications
2
52
1
Order By: Relevance
“…678 8a,d), suggesting the microbiological community was similar during both periods of 679 deposition or during later colonisation. If the former, this is unexpected given the wetter 680 conditions and presumably greater methane cycling (as inferred from hopane  13 C values) in 681 the upper section, although Sherry et al (2016) showed that there was no significant 682 changes in the overall methanotrophic community distribution in sediment slurry incubations 683 under a range of methane concentrations. Nonetheless, the blocky lignite is associated with 684 generally higher proportions of aminopentol (Fig.…”
Section: Variability In Methanotrophic Sources 638mentioning
confidence: 98%
“…678 8a,d), suggesting the microbiological community was similar during both periods of 679 deposition or during later colonisation. If the former, this is unexpected given the wetter 680 conditions and presumably greater methane cycling (as inferred from hopane  13 C values) in 681 the upper section, although Sherry et al (2016) showed that there was no significant 682 changes in the overall methanotrophic community distribution in sediment slurry incubations 683 under a range of methane concentrations. Nonetheless, the blocky lignite is associated with 684 generally higher proportions of aminopentol (Fig.…”
Section: Variability In Methanotrophic Sources 638mentioning
confidence: 98%
“…Temporal profiles of methane removal in the early phase of incubations were consistent with the experiments described by Sherry et al . () with rapid removal of all added methane suggesting comparable methanotroph growth. After methane removal, headspace gas compositions diverged markedly with 50°C incubations showing rapid and extensive re‐emergence of methane (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…At 40°C, aminotriol and aminotetrol were not enriched (Fig. A and B) suggesting that the different Methylobacter species selected for (Sherry et al ., ) produced a low abundance of this compound. Likewise, the thermophilic genus Methylocaldum at 50°C (Sherry et al ., and Supporting Information Table S2) did not produce aminotriol and aminotetrol suggesting their production is restricted to lower temperatures.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations